Androgens Profile in Blood Serum and Follicular Fluid of Women With Poor Ovarian Response During Controlled Ovarian Stimulation Reveals Differences Amongst POSEIDON Stratification Groups: A Pilot Study - Fuentes, Ariel; Sequeira, Karina; Tapia-Pizarro, Alejandro; Muñoz, Alex; Salinas, Abril; Céspedes, Pablo; Escalona, Javier; Godoy, Ana (Frontiers in Endocrinology, 2019)
Patients with poor ovarian response (POR) to exogenous gonadotropins stimulation for assisted reproductive technology (ART) have decreased circulating androgens during spontaneous cycles. The Patient-Oriented Strategies Encompassing Individualized Oocyte Number (POSEIDON) is a 4-tier stratification of women with POR to controlled ovarian stimulation (COH) based on age and biomarkers of ovarian reserve has been proposed to maximize the clinical management of this group for ART. The aim of the present study was to characterize the levels of androgens during COH in follicular fluid (FF) and serum in POSEIDON subgroups and compared them with women of normal ovarian response. Sixty nine consecutive patients undergoing ART were included and testosterone, androstenedione, dehydroepiandrosterone sulfate (DHEA-S), estradiol, sex hormone-binding globulin (SHBG) and insulin-like growth factor 1 (IGF-1) were measured in serum and FF collected at the time of oocyte pick-up. The number of retrieved oocytes was registered for each patient for their allocation to the respective POSEIDON subgroup. The control group comprised 19 women and the POSEIDON group 1 (age < 35, normal ovarian reserve biomarkers) n=14, group 2 (age ≥ 35, normal ovarian reserve biomarkers) n=8, group 3 (age < 35, poor ovarian reserve biomarkers) n=6 and group 4 (age ≥ 35, poor ovarian reserve biomarkers) n=22. Serum levels of total testosterone, androstenedione and DHEA-S were not different in group 1 vs. control but significantly decreased in group 3 vs. control. DHEA-S in FF was also significantly decreased in group 3 vs. control. In addition, serum testosterone was decreased in groups 2 and 4 vs. control; and serum androstenedione and estradiol were reduced in group 4 vs. control. No differences were observed for estradiol, SHBG and IGF-1 in FF. Finally, a high correlation between serum and FF DHEA-S was observed when data from samples of all groups were pooled. Group 1 did not show hypoandrogenemia however group 3 had low levels of all measured androgens in serum and DHEA-S in follicular fluid. Such differences might help to better characterize and/or improve the clinical management of women with POR according to their respective POSEIDON stratification.